DETERMINATION OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR AND PERFORMANCE: ANALYSIS OF JOB SATISFACTION AND WORK ENVIRONMENT (LITERATURE REVIEW OF HUMAN RESOURCE MANAGEMENT) - Yulianto, Latif (Dinasti International Journal of Management Science, 2022)
This study aims to determine the effect of job satisfaction and work environment on Organizational Citizenship Behavior (OCB) and performance. This research is a case study on the State Civil Apparatus (ASN). Performance is an important factor for ASN for service satisfaction to the community, therefore OCB needs to be owned by ASN because OCB is believed to be interrelated with employee performance. This research was conducted to build hypotheses that are useful for further research. This article reviews the variables that affect OCB and performance. The result of this library research article is that job satisfaction and work environment affect OCB and ASN performance.